Diagnostic Value of Faecal M2PK and FIT in Colorectal Cancer Screening - Farahnaz Joukar; Mohammad Saghafi; Sara Yeganeh; Soheil Hassanipour; Fariborz Mansour-Ghanaei (Caspian Journal of Health Research)
Background: The mortality rate of colorectal cancer could be declined by immediate diagnosis. Objectives: We surveyed the potentials of two diagnostic methods, M2 pyruvate kinase (M2PK) and fecal immunochemical tests (FIT), in comparison to colonoscopy as the golden standard strategy. Methods: This cross-sectional study was carried out in 2018 in the north of Iran. Stool samples were taken from 768 subjects. A total of 384 people were tested for M2PK and 384 for FIT. M2PK was evaluated by ELISA (ScheBo kit, Germany), and the FIT was performed immunologically. Then, Colonoscopy was performed on all people. Finally, sensitivity, specificity, positive, and negative predictive values were computed. Results: The mean age of participants was 51.5±14. 6 years. In this population, 68% of people had lesions in colonoscopy. Occult blood in M2PK and FIT test were 64.6 (U/ML) and 65.9 (ng/mL), respectively. The sensitivity, specificity, positive and negative predictive values of M2PK were 72.6%, 87.18%, 82.1%, and 79.7%, respectively. Correspondingly, the results of FIT were 67.1%, 37.1%, 71.9 %, 32.0% respectively. Conclusion: This study showed that the M2PK test had higher sensitivity and specificity compared to FIT. Considering that nowadays non-invasive tests like M2PK are cost-effective and easy to perform than colonoscopy, they can be used in the first stage of screening and this can be a great step in monitoring individuals and identifying pre-cancerous lesions.